"Deceptions Have Been Practiced": Food Standards as Intellectual Property in the Missouri and Ohio Wine Industries (1906–1920). (31st March 2020) - VENTIMIGLIA, ANDREW
Abstract : This article explores early twentieth-century debates about wine regulation in order to understand how emerging food standards could be mobilized in order to produce and protect value around particular geographical locales. Ohio and Missouri winemakers sought to protect their practices of "amelioration, " or the addition of sugar and water to acidic or foxy wines, by establishing the regulatory designation of "Ohio and Missouri Wine" as separate from "Wine." In doing so, they turned food standards into a form of intellectual property mobilized to protect their practices and enhance the market value of Ohio and Missouri wines. Conversely, they argued that "universal" wine standards were unduly preferential to California wines. This compelling yet forgotten historical episode inverts the rationale behind geographical indications (a form of intellectual property designed to protect the intrinsic benefits of place) producing a unique argument for geographical protections based not on value but on lack.